Renal osteodystrophy in the obesity era: Is metabolic syndrome relevant? - Da Silva Martins, Janaina [UNESP]; Castro, João Henrique [UNESP]; Rueda, Nestor A. Sainz; Reis, Luciene Machado dos; Jorgetti, Vanda; Moysés, Rosa Maria Affonso; Caramori, Jacqueline Teixeira [UNESP] (Public Library of Science (PLoS), 2017)
Background Observational studies have shown a beneficial effect of obesity on bone health; however, most of those studies were not based on bone biopsies. Metabolic syndrome (MetS) could have an effect on bone remodeling. However, there are no data on the effects of MetS in the presence of renal osteodystrophy. Objective The aim of this study was to investigate associations between MetS and renal osteodystrophy using the bone histomorphometric turnover-mineralization-volume (TMV) classification. Design, setting, participants & measurements This observational cross-sectional study included 55 hemodialysis patients (28 women/27 men) who were evaluated for MetS and bone histomorphometry. Biochemical parameters included calcium, phosphorus, alkaline phosphatase, intact parathyroid hormone (iPTH), 25-hydroxyvitamin D, free serum leptin, fibroblast growth factor 23 (FGF23), intact osteocalcin, sclerostin (Scl), glucose, insulin, and thyroid hormones. Robust models of multivariate linear regressions were used for the statistical analyses. Results Females had higher iPTH levels (1,143 vs. 358, p = 0.02). Patients with normal bone volume (BV/TV) had a higher prevalence of MetS (73.6% vs. 41.7%, p = 0.02) and higher serum phosphorus, C-terminal FGF23 and insulin levels. The multivariate regression analysis showed that low-density lipoprotein cholesterol (LDL) was positively correlated with bone formation rate (BFR/BS) and negatively associated with mineralization lag time. Bone volume was negatively associated with age but positively associated with MetS. Body mass index (BMI) was not correlated with any of the bone histomorphometric parameters. Conclusion Our results suggest that MetS is not a risk factor for low bone volume in hemodialysis patients. Furthermore, BMI alone was not related to bone volume in this population.